HR Outsourcing: A Quick Way to Expertise - Oberoi, Shalina; Kaushik, Neeraj; Kaushik, V. K. (Prabandhan: Indian Journal of Management, 2010)
Wikipedia defines Outsourcing as subcontracting a process, such as product design or manufacturing, to a third-party. Alternatively, it may be understood as purchasing of service from an outside vendor rather than using internal resources. Human Resources (HR) outsourcing sector is on the rise and India is expected to be one of the major players in this sector. In today's competitive&global market, main focus of any company is to find out the ways to reduce cost without compromising with the quality. HR outsourcing is the process in which a company uses the services of a third party to take care of its HR functions. A company may outsource a few or all of its related activities to a single or combinations of service providers located in offshore destinations like India, China, Philippines.Human Resource Outsourcing is beneficial for an organization in terms of cost-savings, increasing speed, service quality and process standardization. To identify the core and non-core processes that can be outsourced is the key for outsourcing. It frees the company from the burden of recruiting, training, development, and employee orientation programs. Therefore, companies feel more convenient to outsource their HR functions and thus concentrate more on their core business. According to the needs of an organization, there's specialized HR outsourcing firm in that domain. Businesses which outsource their HR functions are generally small-to-midsize firms having employees between 25 to 1500.HR Outsourcing seems to be a strategic tool for businesses which relives them from their HR responsibilities and enables them to focus on their core competencies. Companies can save 30-40% of their cost by outsourcing their HR processes. In a business like HR outsourcing, where information is sensitive&cash flows are high, credibility and reliability are the foundations on which a relationship can be established.There is a continuous increase in the number of companies which outsource their HR activities.